Global trends of gamification in enhancing students’ social skills in physical education (2015–2025) - Rusdiyanto, Rajip Mustafillah; Kurniawan, Ari Wibowo (CV Rezki Media, 2025)
Background: The development of digital technology has triggered a more interactive learning transformation through gamification, namely using game elements to increase students' motivation, engagement, and social skills, such as cooperation, communication, empathy, and problem solving. Objectives: This study aims to analyze global research trends on gamification in enhancing students' social skills, particularly in physical education, through a bibliometric analysis from 2015 to 2025. Methods: This study employed a bibliometric design. Data were retrived from the Scopus database on April 22, 2025, using specific keywords: (gamification OR gamified learning OR game-base-based learning) AND (